Combating Economic Crimes in Iraqi Legislation - Khuraibet Khalaf, Lect .Dr. Zuhair (Basra studies journal, 2025)
Countries achieve prosperity and progress through strong economies, which represent the lifeblood and essential foundation for ensuring the welfare, freedom, and dignity of their people. However, this vital sector is not immune to unlawful exploitation and criminal behavior. Economic crimes are among the most serious challenges confronting a country’s economic policy due to their significant impact on economic and social stability. Accordingly, the state must respond through legislative means to combat perpetrators of such crimes and limit their occurrence by adopting a criminal policy that aligns with the rapid and modern developments in global economic activity and trade. This has led to the emergence of regulatory frameworks, guidelines, and penal laws aimed at upholding justice in this domain. Nevertheless, these laws are not without legislative shortcomings, prompting a need to review and reflect on effective ways to address these deficiencies. This includes proposing amendments and offering recommendations that may contribute to updating the legal framework in line with contemporary developments in the economic field.